Efforts to Improve Writing Skills of High School Students - Nurul Inayah; Rizki Putri Nanda (Universitas Syiah Kuala, 2016)
Writing in English is one of the language skills that are taught in the context of learning English as a Foreign Language (EFL) in Indonesian senior high schools. According to previous studies, most of the students consider writing is the most difficult of the four skills. This research was aimed at finding out the main difficulties in writing faced by the grade XI students at SMA Negeri 10 Fajar Harapan, Banda Aceh, and the efforts made by their teacher to overcome those problems. The design of this study was a descriptive qualitative study. To obtain the data, the writers used document collection and interviews. The results from the document collection showed that the highest percentages of problems faced by the students were in the aspect of language use and the least problems were in the aspect of content. The results from the interviews showed that the most common correcting efforts made by the teacher were giving written feedback for all aspects of writing i.e. language use, mechanics, vocabulary, organization, and content. Likewise, teachers need to develop systemized forms of feedback and make it clear to students what the feedback means and what they are to do with them to assist students in improving their writing skills.